Conditions Promoting Mycorrhizal Parasitism Are of Minor Importance for Competitive Interactions in Two Differentially Mycotrophic Species - Friede, Martina; Unger, Stephan; Hellmann, Christine; Beyschlag, Wolfram (Frontiers in Plant Science, 2016)
Interactions of plants with arbuscular mycorrhizal fungi (AMF) may range along a broad continuum from strong mutualism to parasitism, with mycorrhizal benefits received by the plant being determined by climatic and edaphic conditions affecting the balance between carbon costs vs. nutritional benefits. Thus, environmental conditions promoting either parasitism or mutualism can influence the mycorrhizal growth dependency (MGD) of a plant and in consequence may play an important role in plant-plant interactions. In a multifactorial field experiment we aimed at disentangling the effects of environmental and edaphic conditions, namely the availability of light, phosphorus and nitrogen, and the implications for competitive interactions between Hieracium pilosella and Corynephorus canescens for the outcome of the AMF symbiosis. Both species were planted in single, intraspecific and interspecific combinations using a target-neighbor approach with six treatments distributed along a gradient simulating conditions for the interaction between plants and AMF ranking from mutualistic to parasitic. Across all treatments we found mycorrhizal association of H. pilosella being consistently mutualistic, while pronounced parasitism was observed in C. canescens, indicating that environmental and edaphic conditions did not markedly affect the cost:benefit ratio of the mycorrhizal symbiosis in both species. Competitive interactions between both species were strongly affected by AMF, with the impact of AMF on competition being modulated by colonization. Biomass in both species was lowest when grown in interspecific competition, with colonization being increased in the less mycotrophic C. canescens, while decreased in the obligate mycotrophic H. pilosella. Although parasitism-promoting conditions negatively affected MGD in C. canescens, these effects were small as compared to growth decreases related to increased colonization levels in this species. Thus, the lack of plant control over mycorrhizal colonization was identified as a possible key factor for the outcome of competition, while environmental and edaphic conditions affecting the mutualism-parasitism continuum appeared to be of minor importance.